UTILIZATION OF TOOLS ON THE INTERNET AS AN EFFORT TO INCREASE BRAND IN UKM UD QOQOM FOODS - Amin Hou (Jurnal Ekonomi, 2023)
Awareness in building Branding on products is a strength for SMEs to survive in competition. Technological developments have resulted in more and more people using the internet, such as using social media in their daily lives. This has created a new gap for SMEs to look for new ways to improve the UKM brand, this research uses a sample of 100 where all of them are consumers of Medan Qoqom Food products, for data processing the multiple regression method is used where this research shows that overall research variables Based on the results of tests carried out with linear regression analysis Simultaneous hypothesis testing (Test F) obtained an Fcount of 35,422 This means that together the independent variables consist of social media variables, Viral, influencers, hashtags and google trends have a significant effect on the SME Brand variable